Dans le jardin obscur : Alain DUAULT et Monique W. LABIDOIRE Libre conversation sur la poésie - Bouraoui, Hédi (Revue CMC Review, 2016)
This is Hédi Bouraoui’s commentary on a dialogue between two poets, Alain Duault and Monique W. Labidoire, about their craft.